Psychological impact of post-migration spatial change on vulnerable groups - Kaplan, V.; Melikoğlu, Ya; Paça, M. (Extreme Psychology and Personal Safety, 2025)
Abstract only Context and relevance. Migration is a process that has many physical, social and psychological effects on the individual and societal level. Risk factors such as war, famine, education, economic inadequacies and natural disasters cause forced or voluntary migration. Various cultural, economic and spatial changes occur after migration. These changes have many individual, familial and social effects. The effects of spatial changes on individuals, especially after migration, are quite remarkable. Vulnerable groups consisting of women, children and elderly individuals are much more affected by spatial changes because they are sensitive and defenseless. The access of these groups to basic services such as shelter, nutrition, health and education is greatly restricted after migration. Factors such as uncertainties about the future, economic difficulties, cultural adaptation problems and social exclusion cause psychological problems such as stress, anxiety, eating disorders and depression to become widespread in these groups. Therefore, it is of great importance to determine the psychological effects of spatial changes after migration on vulnerable groups and to provide the necessary intervention and support. In this context, our study provides a literature summary to examine especially vulnerable groups after migration in this context Контекст и актуальность. Миграция - это процесс, который оказывает большое физическое, социальное и психологическое воздействие на человека и общество в целом. Такие факторы риска, как война, голод, проблемы с образованием, экономическая нестабильность и стихийные бедствия, вызывают вынужденную или добровольную миграцию. После миграции происходят различные культурные, экономические и пространственные изменения. Эти изменения имеют множество индивидуальных, семейных и социальных последствий. Влияние пространственных изменений на людей, особенно после миграции, весьма заметно. Уязвимые группы населения, к которым относятся женщины, дети и пожилые люди, гораздо сильнее страдают от пространственных изменений, поскольку они чувствительны и беззащитны. После миграции доступ этих групп к базовым услугам, таким как жилье, питание, здравоохранение и образование, значительно ограничен. Такие факторы, как неопределенность в отношении будущего, экономические трудности, проблемы культурной адаптации и социальная изоляция, приводят к тому, что в этих группах широко распространены такие психологические проблемы, как стресс, тревога, расстройства пищевого поведения и депрессия. Поэтому очень важно определить психологическое воздействие пространственных изменений после миграции на уязвимые группы и обеспечить необходимое вмешательство и поддержку. В этом контексте в нашем исследовании приводится обзор литературы, в которой рассматриваются особенно уязвимые группы после миграции в этом контексте.